2021
DOI: 10.1007/s12070-021-02499-8
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Study of Smell Disorders in COVID-19 Patients in a Tertiary Care Hospital in Pondicherry: A Cross Sectional Study

Abstract: Anosmia and ageusia are the first and maybe the only symptom in patients affected with COVID-19 especially if the patient is paucisymptomatic. This aim of this study was to determine the demographic details of patients with anosmia, prevalence of anosmia and the time taken for it to resolve in patients who are positive for COVID-19 and took treatment in our hospital. Cross Sectional Study. Patients with real time polymerase chain reaction (RTPCR) positive nasopharyngeal and oropharyngeal swabs, who met the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…10,11 F I G U R E 1 Four weeks recovery rate in patients with (+) and without (À) nasal discharge, headache, ageusia, and smoking range could be due to the variation in the race, sample size, patient age, hospitalization, presence of other symptoms and comorbidities, and disease severity. 12 In the current study, the rate of recovery by 4 and 8 weeks was 88.51% and 93.19%, respectively, which was in line with previous studies. In previous studies, recovery rates varied based on the follow-up period.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10,11 F I G U R E 1 Four weeks recovery rate in patients with (+) and without (À) nasal discharge, headache, ageusia, and smoking range could be due to the variation in the race, sample size, patient age, hospitalization, presence of other symptoms and comorbidities, and disease severity. 12 In the current study, the rate of recovery by 4 and 8 weeks was 88.51% and 93.19%, respectively, which was in line with previous studies. In previous studies, recovery rates varied based on the follow-up period.…”
Section: Discussionsupporting
confidence: 92%
“…13 Karthikeyan et al reported 88% recovery in a 5-week follow-up period. 12 In another study, the 2-week recovery rate of anosmia was 63.69%. 11 In the current study, 9.8% of patients experienced anosmia as the first symptom of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 92%
“…These 40 studies (reporting on 43 cohorts) were subjected to a meta-analysis (Table ). Fifteen studies reported anosmia prevalence in 18 cohorts with a total of 7247 COVID-19 patients from regions where the D614 virus was dominant: three studies from Kuwait or Singapore and 12 from India or Pakistan. We compared such data with the results obtained in 25 studies reporting on 25 cohorts with a total of 9626 South Asian patients from the Indian subcontinent (India and Bangladesh) and Oman, when the G614 virus had become dominant (Table , illustrated in Figure A and B). , The differences in results between the two types of cohorts are shown in the forest plots (Figure A). The pooled prevalence of olfactory dysfunction in the same ethnicity (South Asians) in regions with D614 predominance was 5.33% (95% confidence interval, CI = 3.52–8.00%), while in regions with G614 predominance, it was 31.79% (95% CI = 23.26–41.76%) (Figure A, C).…”
Section: Resultsmentioning
confidence: 99%
“…in cases of adult Refsum's disease) [38]. While attempts have been made to develop accurate tests, research has accelerated significantly during the COVID-19 pandemic and pre-screening and widespread smell testing have been proposed, as they may be predictive of a positive COVID-19 test [39][40][41].…”
Section: Smellmentioning
confidence: 99%